SIMULTANEOUS ESTIMATION OF DRUGS PRESENT IN MICROBEADS FOR COLON-TARGETED DRUG DELIVERY SYSTEM - ABHISHEK KUMAR; MEENAKSHI BHARKATIYA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The present study was aimed to develop Eudragit S100 coated colon-targeted sustained-release formulations of alginate-pectin and alginate-hydroxypropyl methylcellulose microbeads containing norfloxacin (NF) and tinidazole (TZ) for the treatment of amebiasis which was simultaneous estimated. Methods: Taguchi L9 orthogonal array design has been used to optimize the composition and operating conditions for the preparation of formulations. Nine batches (P1-H5) were prepared by taking three independent variables (X1 – drug:polymer ratio, X2 – concentration of sodium alginate, and X3 – curing time) at three levels (1, 2, and 3). Response variables studied for batches (P1-H5) were mean particle size (μm) (Y1), drug entrapment efficiency (% w/w) (Y2), and drug loading (% w/w) (Y3). NF and TZ were simultaneous estimated by ultraviolet spectrophotometric method. Drug-polymer compatibility study was carried out by differential scanning calorimetry and Fourier-transform infrared spectroscopy and indicates no physicochemical interaction. Results: Microbeads were analyzed for morphological characteristics, mean particle size, drug entrapment efficiency, drug loading, and in vitro drug release. The average size of optimized alginate-pectin microbeads was found to be 881±0.05 μm with an entrapment efficiency of 78.50±0.28% (NF) and 86.50±0.32% (TZ) which was simultaneous estimated. Conclusion: The studies concluded that formulated enteric-coated alginate-pectin microbeads after enteric coating can be used effectively for the delivery of NF and TZ to colon.